The neglected needs of care leavers in the criminal justice system: Practitioners' perspectives and the persistence of problem (corporate) parenting. (April 2017) - Fitzpatrick, Claire; Williams, Patrick
The link between experiences of care and criminal justice systems is well documented, yet curiously neglected in policy and practice. While the over-representation of care leavers in the justice system is often taken as given, there has been negligible change in policy and practice that appropriately responds to the needs of these individuals. Drawing on interviews with practitioners, this article highlights a series of organizational and institutional barriers to implementing a unique intervention. More broadly, such barriers contribute to the persistence of care(less) practice, facilitating the neglect of care leavers' needs to a system dominated by risk. It is argued that the continued inertia within this area can only be construed as practice negligence and an affront to justice.